Evaluation of the safety and feasibility of resuscitative endovascular balloon occlusion of the aorta. Issue 5 (May 2015) - Saito, Nobuyuki; Matsumoto, Hisashi; Yagi, Takanori; Hara, Yoshiaki; Hayashida, Kazuyuki; Motomura, Tomokazu; Mashiko, Kazuki; Iida, Hiroaki; Yokota, Hiroyuki; Wagatsuma, Yukiko
<x xml:space="preserve">Abstract</x> BACKGROUND Resuscitative endovascular balloon occlusion of the aorta (REBOA) is one of the ultimately invasive procedures for managing a noncompressive torso injury. Since it is less invasive than resuscitative open aortic cross-clamping, its clinical application is expected. METHODS We retrospectively evaluated the safety and clinical feasibility of REBOA (intra-aortic occlusion balloon, MERA, Tokyo, Japan) using the Seldinger technique to control severe hemorrhage. Of 5, 230 patients admitted to our trauma center in Japan from 2007 to 2013, we included 24 who underwent REBOA primarily. The indications for REBOA were a pelvic ring fracture or hemoperitoneum with hemodynamically instability and impending cardiac arrest. Emergency hemostasis was performed during REBOA in all patients. RESULTS All 24 patients had a blunt injury, the median age was 59 (interquartile range, 41–71 years), the median Injury Severity Score (ISS) was 47 (interquartile range, 37–52), the 30-day survival rate was 29.2% (n = 7), and the median probability survival rate was 12.5%. Indications for REBOA were hemoperitoneum and pelvic ring fracture in 15 cases and overlap in 8 cases. In 10 cases of death, the balloon could not be deflated in 5 cases. In 19 cases in which the balloon was deflated, the median duration of aortic occlusion was shorter in survivors than in deaths (21 minutes vs. 35 minutes, p = 0.05). The mean systolic blood pressure was significantly increased by REBOA (from 53.1 [21] mm Hg to 98.0 [26.6] mm Hg, p < 0.01). There were three cases with complications (12.5%), one external iliac artery injury and two lower limb ischemias in which lower limb amputation was necessary in all cases. Acute kidney injury developed in all three cases, but failure was not persistent. CONCLUSION REBOA seems to be feasible for trauma resuscitation and may improve survivorship. However, the serious complication of lower limb ischemia warrants more research on its safety. LEVEL OF EVIDENCE Therapeutic/care management, level V.